Dampak Materialisme, Pengendalian Diri dan Motivasi pada Perilaku Pengelolaan Keuangan Keluarga (Studi pada Masyarakat di Desa Ladang Panjang Kecamatan Sarolangun Kabupaten Sarolangun) - Hamdiah; Febby Nanda Utami; Suci Wulandari (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This study aims to analyze the influence of materialsm, self-control, and motivation on family financial management behavior in the community of Ladang Panjang village, Sarolangun District, Sarolangun Regency. Amid modernization and a growing consumerist lifestyle, rural communities are also experiencing shifts in value orientation that impact household financial behavior. The research method use is a survey with descriptive qualitative approach, involving 60 purposively selected respondents. Data were collected through observation and questionnaires based on indicators of each variable. The result show that materialsm negatively affects financial management behavior, while self-control and motivation play a positive role in encouraging wise financial decisions. These three variables interact and jointly influence the quality of family financial management. The findings highlight the importance of contextual fianncial education and instilling long-term planning values within households to improve economic resilience.